Imidazole derivative with an intramolecular hydrogen bond as thermal latent curing accelerator for epoxy/phenolic resins. Issue 14 (14th November 2021) - Wei, Wei; Gou, Haolan; Sun, Xin; Fei, Xiaoma; Li, Xiaojie; Liu, Xiaoya
Abstract: One‐component epoxy systems with long shelf life during storage or transportation, while high curing reactivity during molding as well as satisfactory mechanical and thermal performances after curing, are extremely essential for industrial application. Herein, we used salicylaldehyde and o ‐phenylenediamine to synthesize 2‐(2′‐hydroxyphenyl)‐1 H ‐benzimidazole (HPBI), an imidazole derivative with an intramolecular hydrogen bond between the phenolic hydroxyl group and the pyridine‐type nitrogen atom of imidazole ring, and further employed HPBI as a thermal latent curing accelerator for epoxy/phenolic resins. The intramolecular hydrogen bond endowed HPBI with inert activity toward resins at room temperature, making the one‐component resin system a long‐term storage stability (21 days of shelf life at 30°C). Once rising the temperature to a high degree, a rather high activity of HPBI to accelerate the curing process of epoxy/phenolic resins. It was attributed to the effective release of high activity of the pyridine‐type nitrogen by breaking the intramolecular hydrogen bond at high temperature. In addition, the resulted thermosets from HPBI also possessed the comparable T g (>130°C, determined by DMA) and thermostability ( T d‐5%  > 380°C) with that from common curing accelerators. Therefore, HPBI was proved to be a promising thermal latent curing accelerator applied in electronic packaging field. Abstract : The imidazole derivative (HPBI) with an intramolecular hydrogen bond was obtained and further developed as a thermal latent curing accelerator for epoxy/phenolic resins. Compared to the common curing accelerators, HPBI possessed the highest activity to accelerate the curing process of epoxy/phenolic resins at high temperature, whereas the one‐component resin composition has long‐term storage stability (approximately 3‐weeks' shelf life) at 30ºC. In addition, the obtained thermosets using HPBI also exhibited the comparable Tg (greater than 130ºC) and thermostability (Td‐5% > 380ºC) with that using common curing accelerators.